A study of insurance problems faced by the insurers, the policyholders and salespersons in Kuala Lumpur / Mary John...[et al.] - John, Mary; Septimus, Daisy; Gindug, Sarlona Jasnie; Suaidi, Isah; Tom Embayan, Zachary; Annuar, Wan Hairol (1986)
The research traces briefly the insurance history, its industry and legislations in Malaysia. It also gives brief description of the authorised bodies related to insurance. This study is carried out within the area of Kuala Lumpur. In the Methodology, officials from the authorised bodies related to insurance and two personnels from an insurance company were met for interviews and supplementary articles. The respondents are the insurers, policyholders and salespersons/agents who were selected randomly to answer the questionnaire.